Kritischer Nachruf‘ – eine neue Textsortenvariante? - Anna Hanus (Colloquia Germanica Stetinensia, 2016)
Despite, or perhaps because of the fact that the obituary is in the area of interest of several research disciplines, it is regarded as a still inadequately examined category. From the point of view of linguistic genology concerning the German studies of this text type, scholars are not unanimous on the status of the obituary, its functional and thematic features and definitional parameters. Furthermore, both in printed and electronic press one can increasingly find texts provided with an annotation ‘critical obituary’ in the title. Does it mean that beside the obituary there has been established a new category? The author of this article aims to describe the concept of the obituary, discuss it from different perspectives, and on the basis of selected press releases, examine whether it is possible to talk about differentiating a new variant of text type.